Effect of lavender essence inhalation on the level of anxiety and blood cortisol in candidates for open-heart surgery - SeyedAbedin Hosseini; Alemeh Heydari; MohammadAli Vakili; Shahram Moghadam; SadeghAli Tazyky (Wolters Kluwer Medknow Publications, 2016)
Background: Surgery, as a treatment, is a stressful experience. The anxiety is more severe in open-heart surgery patients due to its risk and complications. The present study aimed to determine the effect of lavender essence on the levels of anxiety and blood cortisol in candidates for open-heart surgery. Materials and Methods: This was a single-blind clinical trial, a random allocation study with a control group conducted on 90 candidates for open-heart surgery in two groups of study and control. The study and control groups inhaled two drops of lavender and distilled water for 20 min, respectively. Spielberger questionnaire was filled by the patients. A 2 ml blood sample was taken to measure the cortisol level and patients' vital signs were recorded before and after intervention. Data were analyzed by chi-square in the form of mean, SD, and frequency distribution, independent t-test, paired t-test, and analysis of covariance (ANCOVA), with a significance level of P = 0.05 to modify the pre-test scores. Results: Results showed a significant reduction in mean anxiety score from 56.73 (5.67) to 54.73 (5.42) after intervention in the study group, compared to the control group [1.11 (1.17)] (P < 0.001). There was also a higher difference in cortisol level in the study group compared to the control group [1.88 (0.56) vs. 0.42 (0.45)]. ANCOVA test showed that the 10.8% variance in anxiety score and 69.6% decrease in blood cortisol resulted from inhalation of lavender. Conclusions: Results showed the positive effect of lavender essence on anxiety and blood cortisol level among the patients. Aromatherapy with lavender is suggested to be considered as a nursing intervention in clinical settings.